2001
DOI: 10.1139/v01-167
|View full text |Cite
|
Sign up to set email alerts
|

Geometric and solvent effects on intramolecular phenolic hydrogen abstraction by carbonyl n,π* and π,π* triplets

Abstract: The photochemistry of a series of alkoxyacetophenone, -benzophenone, and -indanone derivatives, which contain a remote phenolic group linked to the ketone by a para,para¢-or meta,meta¢-oxyethyl spacer, has been studied in acetonitrile and dichloromethane solutions using laser flash photolysis techniques. The corresponding methoxysubstituted compounds and, in the case of the alkoxyindanones, derivatives bearing just a remote phenyl substituent, have also been examined. The triplet lifetimes of the phenolic comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…Figure 3 shows Hammett plots of the rate constants for quenching of the triplet states of the substituted benzophenones and acetophenones by 4MP in MeCN solution. Of the 14 benzophenones included in the plot for that series of compounds, data for nine of them were already available from earlier studies (16, 22, 24). The five new compounds studied in the present work were chosen with specific reasons in mind.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 3 shows Hammett plots of the rate constants for quenching of the triplet states of the substituted benzophenones and acetophenones by 4MP in MeCN solution. Of the 14 benzophenones included in the plot for that series of compounds, data for nine of them were already available from earlier studies (16, 22, 24). The five new compounds studied in the present work were chosen with specific reasons in mind.…”
Section: Discussionmentioning
confidence: 99%
“…Although phenolic hydrogen abstraction by aromatic carbonyl compounds has continued to be of interest in recent years (18–29), there have been no studies reported that probe the trends in the kinetics of the reaction in nonaqueous solvents as a function of the structural and electronic properties of the ketone in an extensive and systematic way. Accordingly, in the present paper we report the results of a survey of the absolute rate constants for reaction of the lowest triplet states of nearly 40 aromatic ketones with a single phenol ( para ‐methylphenol) in acetonitrile (MeCN) solution at room temperature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The implications of the presence of such light-absorbing organics and the possible photochemical reactions are not yet well understood in the sea surface microlayer. But clearly, the presence of such photoactive compounds at the air/sea interfaces could give rise to photosensitized processes (Becker et al, 1995;Canonica et al, 2006Canonica et al, , 2000Canonica et al, , 2005Das et al, 1981;Ivanov et al, 2005;Lathioor and Leigh, 2001;Lathioor et al, 1999;Leigh et al, 1996) which may also affect chemistry in the marine boundary layer (MBL) (Reeser et al, 2008). Previously, we showed that chlorophyll may be a photochemical source of halogenated radicals or the driving force for ozone deposition at low wind speed (Clifford et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In the latter case the reaction occurs by a hydrogen atomtransfer mechanism, whereas, in the former, the mechanism passes through a hydrogen-bonded complex and involvement of the relatively basic * triplet state has been suggested. 9 In this work we report the results of a systematic study of the reactivity of 1,2-aceanthrylenedione (1) in the presence of substituted phenols employing the laser flash photolysis technique.…”
mentioning
confidence: 99%